The Centaurea parlatoris complex (Asteraceae): taxonomic checklist and typifications - Domina, Gianniantonio; Barone, Giulio; Di Gristina, Emilio; Raimondo, Francesco M. (Phytotaxa, 2021)
A taxonomic account of the Centaurea parlatoris complex (Asteraceae), endemic to Sicily, is presented. This complex includes six taxa, three described in the 19th century (C. parlatoris, C. parlatoris var. tomentosa and C. parlatoris var. virescens) and three recently described (C. sicana, C. giardinae and C. heywoodiana). Starting from the designation of the types for the oldest plant names that have not been typified yet, taxonomic considerations are formulated and C. parlatoris var. virescens is elevated to the rank of species. An identification key and a distribution map complete this account.